2019
DOI: 10.3168/jds.2018-16105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the rumen and colon microbiota and effects of live yeast dietary supplementation during the transition from the dry period to lactation of dairy cows

Abstract: The first objective of this study was to evaluate the dynamics and their potential association with animal performance of the microbiota in both the rumen and colon of dairy cows as they move from a nonlactation to a lactation ration. The second objective was to assess the potential effects on the microbiota of live yeast supplementation. Twenty-one Holstein cows were split in 2 treatments consisting of 1 × 10 10 cfu/d of live yeast (LY; n = 10) or no supplementation (control; n = 11) starting 21 d before unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 63 publications
(70 reference statements)
7
70
0
1
Order By: Relevance
“…Succinivibrionaceae_UCG-002 and Ruminobacter are two genera in the family Succinivibrionaceae , and this family was thought to be sensitive to changes in individual, diet and environment [31,32]. In this study, positive correlations were observed between Succinivibrionaceae_UCG-002 and temperature and between Ruminobacter and temperature, which is in agreement with Bach et al (2019) who found a negative association between Ruminobacter and DMI [33], because DMI decreased with an increase in temperature at similar humidity [34]. However, it is strange that no associations were found between any genus and humidity, perhaps the humidity level in the current study was not enough to highlight the differences, but further studies are required to prove this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…Succinivibrionaceae_UCG-002 and Ruminobacter are two genera in the family Succinivibrionaceae , and this family was thought to be sensitive to changes in individual, diet and environment [31,32]. In this study, positive correlations were observed between Succinivibrionaceae_UCG-002 and temperature and between Ruminobacter and temperature, which is in agreement with Bach et al (2019) who found a negative association between Ruminobacter and DMI [33], because DMI decreased with an increase in temperature at similar humidity [34]. However, it is strange that no associations were found between any genus and humidity, perhaps the humidity level in the current study was not enough to highlight the differences, but further studies are required to prove this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…Other members of the Ruminococcaceae family were found to decline across fermentation samples for Experiment 1 and from the neat rumen fluid to the first sampling point of Experiment 2, but they did recover somewhat by the end of the experiment. Similar to Prevotella, the Ruminococcaceae have been shown to have high functional diversity (Bach et al, 2019), which may explain their reduced abundance within the model. A decline of species from the Prevotella and Ruminococcus genera have been observed previously in an in vitro rumen model (Weimer et al, 2011).…”
Section: A)mentioning
confidence: 98%
“…Prevotella spp. -which belongs to Bacteroidetes-has been associated to feed efficiency (Jewell, McCormick, Odt, Weimer, & Suen, 2015; Bach et al, 2019), although most of these results were not consistent due to the low taxonomic resolution of 16S rRNA gene sequencing. Species among this genus are involved in central rumen processes such as pectin and xyloglucan degradation and acetate production (Seshadri et al, 2018), which have a high impact on the nutrition of ruminants.…”
Section: Discussionmentioning
confidence: 98%
“…Classical approaches for modulating the microbiome include management practices and food additives, genetic selection is the principal strategy to obtain animals with improved phenotypic traits (Tapio, Snelling, Strozzi, & Wallace, 2017). It has been suggested that the microbial composition in ruminants could be used as a predictor of complex traits (Gonzalez-Recio, Zubiria, García-Rodríguez, Hurtado, & Atxaerandio, 2018), as there are signs of host genetic control over the microbiome composition in cows, which could lead to animal breeding programs that select animals with a favorable microbiome for a high feed efficiency phenotype (Sasson et al, 2017). Thus, selecting animals with less methane production could lead to a decrease in the overall impact of livestock in our environment.…”
Section: Discussionmentioning
confidence: 99%